Effect of Ginger Essential Oil Emulsion Coating on the Preservation of Tender Ginger - LÜ Hanjia, LI Yuncheng, LI Qingzhou, CHEN Chuan, LIU Dayu, ZHANG Fei, MENG Fanbing (Shipin Kexue)
This study investigated the preservation of tender ginger using a combination of ginger essential oil (GEO) nano-emulsion coating and vacuum packaging. The nano-emulsion was prepared with konjac glucomannan (KGM), lysozyme (Ly), and Tween 80 as wall materials, and its optimal concentration was determined based on its stability. The effect of wall material composition on the preservation of tender ginger was evaluated by physiochemical and biochemical analyses. The results indicated that the emulsion with 2% GEO was the most stable. Vacuum packaging combined with the KGM + Ly + GEO (KLE) nano-emulsion coating containing 0.5 g of KGM, 0.1 g of Ly, 0.8 g of Tween 80, and 2 g of GEO per 100 mL of emulsion significantly reduced mass loss rate, and prevented enzymatic browning and texture changes of tender ginger. During storage, the levels of total phenols, total flavonoids, and 6-gingerol were increased, which inhibited the activities of peroxidase, catalase, polyphenol oxidase, and phenylalanine ammonia-lyase in tender ginger. Microbiome analysis indicated that the combined treatment effectively reduced the diversity and richness of bacteria and fungi. The dominant microorganisms in tender ginger coated with the KLE nano-emulsion were Latilactobacillus and Rahnella, and the common spoilage microorganism Mucor in tender ginger was effectively inhibited.